Co-Designing the Urban Energy Transition in Sweden (EAAE Annual Conference Proceedings, 2023)
The high ambitions for renewable carbon technologies, increasing electricity demand and technological developments are opening more opportunities in small-scale generation. This may push zero-carbon electricity production closer to the final users/prosumers, of which the majority lives in cities and urbanised areas.